(untitled) (Third Sector Social Economic Review, 2022)
Nowadays economic growth has become dependent on technology and innovation levels with the effect of developments in information and communication technologies. Creative ideas and inventions are the basis of all these processes. Intellectual property rights mean the protection of creative thinking and therefore their impact on innovation and economic growth is important for countries. There is a consensus in the literature that stronger intellectual property protection in developed countries encourages innovation and economic growth. however, it remains unclear how strong intellectual property rights protection will affect innovation and economic growth in middle-income countries where imitation and technology transfer are important. This study aims to analyze the effect of intellectual property rights on economic growth in terms of middle-income countries. The study covers 80 middle-income countries and the developed hypothesis was tested with the panel cointegration method. The research is for the period 1995-2020. The findings of the study indicate that there is a cross-sectional dependence between the countries that make up the panel. While it revealed a statistically insignificant but positive relationship between intellectual property rights and economic growth for the whole panel, in Cameroon, Jamaica, Morocco, Romania, Samoa and Zambia, intellectual property rights had a statistically insignificant but negative effect on the economic growth variable.